EDUKASI GIZI SEIMBANG TERHADAP PERUBAHAN PENGETAHUAN PADA CALON PENGANTIN DI KOTA PEKANBARU - Yessi Alza; Fitriani Fitriani; Hesti Atasasih; Roziana Roziana; Husnul Khotimah (UHAMKA PRESS, 2016)
ABSTRACTNutrition and food is not only necessary for the growth, the development of physical,mental and health, but is also necessary for fertility or fertility in order to get a descent. The stateof maternal nutrition prior to conception inﬂuence on fertilization, fetal health, and maternalhealth. Fetal growth and birth weight of children is strongly inﬂuenced by the nutritional statusof pregnant women, both before and during pregnancy. Mothers with poor nutrition statushas deposits of nutrients is not enough to support the growth and development of the fetusand the mother’s health, as a result of fetal growth retardation, birth defects, miscarriage and low birth weight (LBW). The low nutritional status is affected by the lack of knowledge aboutnutritious food. An action based on knowledge will be better than the deed that is not basedon knowledge. Domain knowledge is very important for the formation of a person’s actions.The purpose of this study was to determine the effect of nutrition education on knowledgeabout balanced nutrition changes on the bride and groom in Pekanbaru. This study was aPre-experimental research design with pre-post test with a total sample of 51 people taken byaccidental sampling. The variables studied were knowledge bride. Data were analyzed usingpaired t test technique with SPSS for Windows version 21. The results showed that there was asignifcant difference (p-value = 0,000) about the average percentage of nutritional knowledgeof respondents between before and after education, the average knowledge before being educated45.9 ± 13.211% increased to 62.37 ± 15.916%.Keywords: education, knowledge balanced nutrition